Incidence of adverse drug reactions in a paediatric ward of a Malaysian hospital: A prospective observational study - Ithnin M.; Rani M.D.M.; Latif Z.A.; Kani P.A.P.; Syaiful A.; Mohd T.A.M.T.; Khairun Nain Nor Aripin (University of Benin, 2024)
Indexed by WOS/SCOPUS